Unwanted Exacerbation of the Immune Response in Neurodegenerative Disease: A Time to Review the Impact - Leite, Amanda de Oliveira Ferreira; Bento Torres Neto, João; dos Reis, Renata Rodrigues; Sobral, Luciane Lobato; de Souza, Aline Cristine Passos; Trévia, Nonata; de Oliveira, Roseane Borner; Lins, Nara Alves de Almeida; Diniz, Daniel Guerreiro; Diniz, José Antonio Picanço; Vasconcelos, Pedro Fernando da Costa; Anthony, Daniel Clive; et al. (Frontiers in Cellular Neuroscience, 2021)
The COVID-19 pandemic imposed a series of behavioral changes that resulted in increased social isolation and a more sedentary life for many across all age groups, but, above all, for the elderly population who are the most vulnerable to infections and chronic neurodegenerative diseases. Systemic inflammatory responses are known to accelerate neurodegenerative disease progression, which leads to permanent damage, loss of brain function, and the loss of autonomy for many aged people. During the COVID-19 pandemic, a spectrum of inflammatory responses was generated in affected individuals, and it is expected that the elderly patients with chronic neurodegenerative diseases who survived SARSCoV-2 infection, it will be found, sooner or later, that there is a worsening of their neurodegenerative conditions. Using mouse prion disease as a model for chronic neurodegeneration, we review the effects of social isolation, sedentary living, and viral infection on the disease progression with a focus on sickness behavior and on the responses of microglia and astrocytes. Focusing on aging, we discuss the cellular and molecular mechanisms related to immunosenescence in chronic neurodegenerative diseases and how infections may accelerate their progression.